Clinical Practice Guidelines for the Immunological Management of Chromosome 22q11.2 Deletion Syndrome and Other Defects in Thymic Development (2023)
ABSTRACT: Current practices vary widely regarding the immunological work-up and management of patients affected with defects in thymic development (DTD), which include chromosome 22q11.2 microdeletion syndrome (22q11.2del) and other causes of DiGeorge syndrome (DGS) and coloboma, heart defect, atresia choanae, retardation of growth and development, genital hypoplasia, ear anomalies/deafness (CHARGE) syndrome. Practice variations affect the initial and subsequent assessment of immune function, the terminology used to describe the condition and immune status, the accepted criteria for recommending live vaccines, and how often follow-up is needed based on the degree of immune compromise. The lack of consensus and widely varying practices highlight the need to establish updated immunological clinical practice guidelines. These guideline recommendations provide a comprehensive review for immunologists and other clinicians who manage immune aspects of this group of disorders.